Necrosis : methods and protocols - McCall, Kimberly, Ed; Klein, Charles, Ed (Methods in molecular biology, 2013)
Cell death is an essential process in development, and a major contributor to a wide range of human diseases. Three major classifications of cell death, apoptosis, autophagic cell death and necrosis, have been described for years, and the existence of many more forms of cell death is now accepted. In, Necrosis: Methods and Protocols experts in the field provide a wide range of methods and techniques for the study of necrosis in vitro and in vivo. These include methods and techniques for the analysis of necrosis in mammalian cells, characterization of alternative forms of cell death: entosis and pyroptosis, and analysis of cell death in non-mammalian model sytems and mammalian tissues, including chapters on skin, brain, and heart. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. -- Publisher website.